Hepatitis B virus total core antibody status in unvaccinated general population in a community of Bangladesh - Ahmed, Mostak U.; Tanu, Sumona; Mithila, Maisha T.; Alam, M. Jahangir; Saha, Madhusudan; Chowdhury, Sadia R.; Safwath, Syed A.; Chowdhury, Malay K. S.; Rahman, M. Oliur; Rahman, M. Muhibur (International Journal of Research in Medical Sciences, 2024)
Background: Hepatitis B virus (HBV) infection poses a significant health challenge in Bangladesh, with the hepatitis B core antibody (anti-HBc) being a crucial marker due to its lifelong presence in the bloodstream. This study aimed to evaluate the prevalence of anti-HBc (total) positivity among unvaccinated adults in Northeastern Bangladesh. Methods: This cross-sectional observational study was conducted in the Sobhanighat area of Sylhet, Bangladesh, in collaboration with the department of gastroenterology, Sylhet MAG Osmani Medical College, from November 2022 to August 2023. A total of 216 participants were selected using consecutive sampling. HBsAg, anti-HBs, and anti-HBc (total) were tested for all subjects, and data were collected using a pre-formed questionnaire and analyzed using statistical package for the social sciences (SPSS) version 24. Results: Among the participants, 16 (7.4%) tested positive for anti-HBc (total), while HBsAg was positive in 6 (2.77%) individuals. Anti-HBs was detectable in 23 (10.6%) participants, with 3 (1.38%) showing isolated anti-HBc positivity. Notably, 20% of HBsAg-positive cases exhibited heterotypic anti-HBs. Moreover, 56.25% of respondents with anti-HBc (total) positivity had detectable anti-HBs (p<0.001). Gender did not show significant associations with HBsAg, anti-HBc (total), anti-HBs, or isolated anti-HBc (p>0.05). Conclusions: The study underscores a notable prevalence of anti-HBc (total) positivity among unvaccinated individuals in Bangladesh, indicative of past HBV exposure. It underscores the necessity for enhanced vaccination coverage and robust infection control measures to mitigate HBV transmission in this demographic.